New records of Tonnoira Enderlein (Diptera, Psychodidae, Psychodinae) from the Brazilian Amazon with descriptions of two new species - Chagas-Vieira, Cínthia (Zootaxa, 2012)
Diagnoses and illustrations are given for Tonnoira bitalea Quate. This species is recorded from Brazil for the first time based on material collected from the state of Amazonas, Ipixuna, Rio Gregório. T. spina sp. nov. and T. tripenis sp. nov. are described and illustrated based on specimens collected from the same locality.